STUDY OF THE POTENTIAL ANAEROBIC CO-DIGESTION FOR BIOGAS PRODUCTION FROM SALVINIA MOLESTA AND RICE STRAW (Jurnal Bahan Alam Terbarukan, 2017)
The purpose of this research was to analyze the biogas production from co-digestion of Salvinia molesta and rice straw. Ratio of Salvinia molesta and rice straw was 5:0, 4:1, 3:2. Lab-scale-batch digesters (600 mL) were operated at room temperature (30 oC) and pressure of 1 atm. Total basis of Salvinia molesta and rice straw was 10 gr, water was added with ratio of organic matter:water = 1:7 (w/w), rumen fluid was added as inoculum, initial pH was adjusted to be 7. Fermentation process was conducted for 30 days. The results showed that total biogas volume for ratio of 5:0, 4:1, 3:2 was 6.30±0.00; 32.76±18.32; 107.54±18.51 mL/g VS respectively. The pH of substrate was changing from 7.00 to 6.77±0.19; 6.60±0.14; 6.73±0.09 for all variables respectively.